Immediate effects of breath holding maneuvers onto composition of exhaled breath - Sukul, Pritam; Trefz, Phillip; Schubert, Jochen K; Miekisch, Wolfram (Journal of breath research, 2014)
Rapid concentration changes due to physiological or pathophysiological effects rather than appearance of unique disease biomarkers are important for clinical application of breath research. Simple maneuvers such as breath holding may significantly affect breath biomarker concentrations. In this study, exhaled volatile organic compound (VOC) concentrations were assessed in real time before and after different breath holding maneuvers. Continuous breath-resolved measurements (PTR-ToF-MS-8000) were performed in 31 healthy human subjects in a side-stream sampling mode. After 1 min of tidal breathing participants held their breath for 10, 20, 40, 60 s and as long as possible. Afterwards they continued to breathe normally for another minute. VOC profiles could be monitored in real time by assigning online PTR-ToF-MS data to alveolar or inspired phases of breath. Sudden and profound changes of exhaled VOC concentrations were recorded after different breath holding maneuvers. VOC concentrations returned to base line levels 10-20 s after breath holding. Breath holding induced concentration changes depended on physico-chemical properties of the substances. When substance concentrations were normalized onto end-tidal CO2 content, variation of acetone concentrations decreased, whereas variations of isoprene concentrations were not affected. As the effects of breathing patterns on exhaled substance concentrations depend on individual substance properties, sampling procedures have to be validated for each compound by means of appropriate real-time analysis. Normalization of exhaled concentrations onto exhaled CO2 is only valid for substances having similar physico-chemical properties as CO2.